NHERFs, NEP, MAGUKs, and More: Interactions That Regulate PTEN - Bonifant, Challice L. (J Cell Biochem, 2007)
This year marks the 10th anniversary of the discovery of the PTEN/MMAC1/TEP1 tumor suppressor gene (hereafter referred to as PTEN), one of the most commonly mutated genes in cancer. PTEN encodes a lipid phosphatase that dephosphorylates phosphoinositide-3,4,5-triphosphate (PIP(3)), thereby counteracting mitogenic signaling pathways driven by phosphoinositol-3-kinases (PI3K). By opposing PI3K signaling, PTEN inhibits the activation of the critical PI3K effector proteins Akt1-3 (also known as protein kinase B or PKB). Given its central role in antagonizing PI3K signaling, one might expect that like PI3K, the activity of the PTEN protein would be highly regulated by numerous protein/protein interactions. However, surprisingly little is known about such interactions. This fact, combined with the generally accepted notion that phosphatases are less exquisitely regulated than kinases, has led to the idea that PTEN may function in a relatively unregulated fashion. Here we review the identities and proposed functions of known PTEN-interacting proteins, and point out avenues of investigation that we hope may be fruitful in identifying important new mechanisms of PTEN regulation in mammalian cells.